Trimester-Specific Dynamics of Haematological, Coagulation, Biochemical And Angiogenic Biomarkers In Pregnancies At Risk Of Early-Onset Preeclampsia: A Prospective Comparative Study Of Early Diagnosis And Complex Treatment - Sharipova Shakhnoza Ulugbekovna; Tuksanova Dilbar Ismatovna (International Journal of Medical Science and Dental Health, 2026)
Background. Preeclampsia (PE) is driven by systemic endothelial dysfunction and an angiogenic imbalance. We characterised the trimester dynamics of haematological, coagulation, biochemical and angiogenic biomarkers and assessed the impact of early diagnosis and complex treatment. Materials and Methods. In this prospective comparative study, 102 pregnant women were allocated to a control group (physiological pregnancy, n=30), an early-diagnosed and treated group (n=32) and an untreated group (n=40). Complete blood count, coagulogram, C-reactive protein (CRP), lactate dehydrogenase (LDH), urea, creatinine, VEGF, TGF-β2, EGF, sFlt-1, PlGF and the sFlt-1/PlGF ratio were measured each trimester. Between-group differences were tested by one-way ANOVA or Kruskal–Wallis with post-hoc correction; longitudinal change by linear mixed models; α=0.05. Results. By the third trimester, untreated women showed anaemia (haemoglobin 80.1±6.2 g/L), thrombocytopenia (150.9±14.2×10⁹/L) and hypercoagulation (fibrinogen 7.6±1.0 g/L; PT 8.7 s). CRP rose 5.2-fold, LDH 2.9-fold (648.9±34.0 U/L), and creatinine reached 107.4±5.4 µmol/L. VEGF fell 2.5-fold while the sFlt-1/PlGF ratio rose 10.6-fold versus controls (all p